The Role of Parents with Javanese Cultural Background in Helping the Learning of Mentally Impaired Children During the Covid-19 Pandemic - Findivia Egga Fahruni; Nabila Salma Salsabila; Najlatun Naqiyah (ELS Journal on Interdisciplinary Studies in Humanities, 2022)
This work points to illustrate the implementation of the role of parents with Javanese cultural backgrounds to support learning in children with intellectual disabilities during the Covid-19 pandemic. This is a qualitative approach using the case study method. There are 3 research subjects, namely one mentally retarded child and one father, and one mother who has a mentally retarded child. Subject selection by purposive sampling. The research placement is in Al Hikmah Islamic Elementary School, which is located in Kajar Gadingwatu Hamlet, Menganti District, Gresik Regency. Gather information through interview techniques and documentation. This study produces data that parents of mentally retarded children have several roles, namely as motivators, educators, facilitators, directors, and supervisors.